Utilizing Digital Technology to Enhance Learning Quality in Salafiyah Pesantren: A Qualitative Case Study - Muhammad Mushfi El Iq Bali; Rizki Ramadani (Information Technology Education Journal, 2025)
Pesantren as a traditional Islamic educational institution in Indonesia, plays a strategic role in shaping the character and intellectual development of its students (santri). However, the dynamics of globalization and advancements in digital technology demand that pesantren innovate their learning models to remain relevant to contemporary needs. The integration of digital technology in pesantren education has become an imperative to improve educational quality, broaden access to learning resources, and strengthen the integration between Islamic values and 21st-century skills. This study aims to explore the role of digital technology in enhancing the quality of learning in pesantren, which have long been known for their conventional teaching methods. The use of digital tools and platforms such as e-learning, educational apps, and social media has demonstrated significant potential in enriching students' learning experiences. This research employs a qualitative approach using case studies of several pesantren that have adopted digital technologies in their learning systems. Data were collected through in-depth interviews, participatory observations, and document analysis related to the learning process. Thematic analysis was used to identify patterns in technology utilization, supporting and inhibiting factors, and its impact on the learning process and outcomes. The findings indicate that digital technology integration enhances student engagement, facilitates access to learning materials, and enriches teaching methods. In conclusion, digitalization in pesantren education offers great potential to improve learning quality, provided it remains aligned with Islamic values and local cultural contexts.